Artemis and p53 cooperate to suppress oncogenic N-myc amplification in progenitor B cells - Rooney, Sean (National Academy of Sciences, 2004)
The nonhomologous DNA end-joining (NHEJ) pathway contains six known components, including Artemis, a nuclease mutated in a subset of human severe combined immunodeficient patients. Mice doubly deficient for the five previously analyzed NHEJ factors and p53 inevitably develop progenitor B lymphomas harboring der(12)t(12;15) translocations and immunoglobin heavy chain (IgH)/c-myc coamplification mediated by a breakage-fusion-bridge mechanism. In this report, we show that Artemis/p53-deficient mice also succumb reproducibly to progenitor B cell tumors, demonstrating that Artemis is a tumor suppressor in mice. However, the majority of Artemis/p53-deficient tumors lacked der(12)t(12;15) translocations and c-myc amplification and instead coamplified IgH and N-myc through an intra- or interchromosome 12 breakage-fusion-bridge mechanism. We discuss this finding in the context of potential implications for mechanisms that may target IgH locus translocations to particular oncogenes.